PSIKOANALISIS SIGMUND FREUD PADA TOKOH UTAMA NOVEL SYAHADAT CINTA KARYA TAUFIQURRAHMAN AL-AZIZY - Husni BT Salam (Cross-border, 2021)
This research is a qualitative descriptive study that aims to describe the main characters in the novel Shahada Cinta by Taufiqurrahman al-Azizy based on the psychological approach of Sigmund Freud. The data in this study are sentences or paragraphs that describe the characters. The data source of this research is the novel Shahada Cinta by Taufiqurrahman al-Azizy. Data collection is done by reading and recording techniques. The research data were analyzed using Sigmund Freud's theory of Literary Psychology. The results of the study of all the data in the novel Shahada Cinta by Taufiqurrahman al-Azizy show that the characters that appear are simple characters and round characters. In this novel, the ego personality system is more prominent, namely the personality component whose task is to find in reality what the id needs as a satisfaction and tension reliever. The main characters try to find and reveal their identity through life experiences and religious teachings. After being analyzed using Sigmund Freud's three personality systems, namely the id, ego, and superego, it turns out that each of the main characters has these three personality systems.